Climate‐smart innovations and rural poverty in Ethiopia: Exploring impacts and pathways - Tesfaye, Wondimagegn; Blalock, Garrick; Tirivayi, Nyasha (Agricultural and Applied Economics Association, 2021)
Climate‐smart innovations have been receiving increasing attention in policy dialogues for their potential to transform agricultural systems and improve the well‐being and resilience of farm households. Using recent panel data from Ethiopia combined with novel historical weather data, we provide microeconomic evidence of the welfare effects of conservation agriculture (CA), a climate‐smart agricultural practice. We use a panel data endogenous switching regression model to deal with selection bias and farmer heterogeneity in CA choice. The study finds that the CA practices that play a pivotal role in addressing the exigencies of rural poverty are minimum tillage, cereal‐legume intercropping, and their combination. These practices reduce the incidence and depth of poverty in areas prone to rainfall stress, which is an indication of their risk mitigation role. In contrast, crop residue retention and its combination with minimum tillage appear not to be economically attractive CA options. The results show that CA portfolios that include minimum tillage and cereal‐legume associations can accelerate efforts to reduce rural poverty and improve climate risk management. We caution against exaggerated expectations of CA's economic benefits and a rigid recommendation of CA.